Role of Artificial Intelligence (AI) in Shaping the Learning Architecture Within Corporations and Small and Medium Enterprises (SMEs) Across the Indian Subcontinent - Vasudevan, Prasanna (Digital Repository of Theses, 2026)
Indian corporate leaders, SMEs, and learners have long faced challenges in identifying learning needs, traditionally relying on roles, hierarchies, and structures. This approach often results in generic learning initiatives. This study explores how AI is reshaping Learning and Development (L&D), empowering individuals to personalize their learning while staying aligned with organizational goals. AI-driven learning solutions are emerging as a strong alternative to traditional service providers, who struggle to differentiate offerings. Organizations now seek innovative approaches to engagement, measurement, customization, and ROI. AI platforms address these needs through personalization, adaptability, and efficiency—facilitating tailored skill development at scale. Historically, access to knowledge was limited to elite networks and institutions. AI democratizes this access, enabling continuous learning and capability building through intelligent, customized tools. These solutions also help organizations reduce time, cost, and effort compared to traditional methods. The study employed a 270-degree data gathering approach, using Zoho Surveys and indepth interviews with senior corporate executives, learning service providers, and learners. It included inputs from 123 learners, five L&D service providers, and senior representatives from 10 companies across sectors like BFSI, Manufacturing, IT & ITES, Education, Pharma, Automobile, Entertainment, and more. Findings reveal growing awareness and willingness to adopt AI in L&D strategies across all groups. Key concerns include data security, job displacement fears, and the complexity of redesigning existing frameworks. Despite this, there is optimism about AI’s ability to simplify learning structures and drive transformation. AI enables a shift from one-size-fits-all models to dynamic, personalized, and goal-oriented learning experiences. Organizations that adopt AI in L&D stand to enhance learning effectiveness, align training with business outcomes, and create measurable impact.